1955
DOI: 10.3181/00379727-89-21721
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thromboplastin Component (PTC) Deficiency Produced by Prolonged Administration of Prothrombopenic Anticoagulants.

Abstract: PTC DEFICIENCY 81 from both normal and diabetic rats responds similarly. The increased glucose-6-phosphatase activity found in liver of alloxan diabetic rats therefore does not appear to be due to any such activation mechanism, but rather due to an actual increase in the amount of enzyme present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1957
1957
1968
1968

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is a short period, in other words, early during dicoumarolization when the prothrombin time is lengthened yet Factor V and prothrombin concentration are high, Stuart factor and PTC levels are not significantly reduced, and the thromboplastin generation test is normal. Later during therapy the Stuart factor becomes reduced along with PTC (44)(45)(46) and prothrombin (47).…”
Section: Properties Of Stuart Factormentioning
confidence: 99%
“…There is a short period, in other words, early during dicoumarolization when the prothrombin time is lengthened yet Factor V and prothrombin concentration are high, Stuart factor and PTC levels are not significantly reduced, and the thromboplastin generation test is normal. Later during therapy the Stuart factor becomes reduced along with PTC (44)(45)(46) and prothrombin (47).…”
Section: Properties Of Stuart Factormentioning
confidence: 99%
“…Prothrombin, factor VII, and the Christmas factor have many properties in common. They are all adsorbed by inorganic precipitates, are all deficient in coumarin therapy (Naeye, 1956;Sise, Kimball, and Adamis, 1955;Douglas and Mair, 1957), and by this study are shown all to be reduced in concentration in vitamin K deficiency, responding at similar rates to the administration of vitamin K. The possibility is further raised that these three components may be more closely identified than is generally envisaged.…”
Section: Resultsmentioning
confidence: 51%
“…13 it is now known that several factors are affected including those involved in the early stages of the intrinsic mechanism. 23 " 25 Since the intrinsic coagulation mechanism is independent of Factor VII ac-Circulation Research. Volume VIII, November I960 tivity, 13 it is not surprising that the prothrombin time is sometimes a poor index of changes in platelets.…”
Section: Platelet Function and Other Clotting Testsmentioning
confidence: 99%